Establishment of a quadruplex real-time PCR assay to distinguish the fungal pathogens Diaporthe longicolla, D. caulivora, D. eres, and D. novem on soybean. - Behnoush Hosseini (Public Library of Science (PLoS), 2021)
Diaporthe species are fungal plant pathogens of many important crops. Seed decay is one of the most important diseases on soybean. It is caused by various species of the genus Diaporthe and responsible for significant economic damage. In central Europe the four species D. longicolla, D. caulivora, D. eres, and D. novem are considered the principal species of Diaporthe on soybean. Fast and accurate detection of these pathogens is of utmost importance. In this study four species-specific TaqMan primer-probe sets that can be combined into a quadruplex assay were designed based on TEF sequences. The specificity and efficiency of the primer-probe sets were tested using PCR products and genomic DNA from pure cultures of the four Diaporthe species and other soybean fungal pathogens. Our results indicate that the primer-probe sets DPCL, DPCC, DPCE, and DPCN allow discrimination of D. longicolla, D. caulivora, D. eres, and D. novem, respectively, and can be used to detect and quantify these four Diaporthe species in parallel using quadruplex real-time PCR. In addition, the quadruplex real-time PCR assay was evaluated on different plant materials including healthy and infected soybean seeds or seed lots, soybean stems, and soybean leaves. This assay is a rapid and effective method to detect and quantify Diaporthe species from samples relevant for disease control.